Proposed new interior design of Women Respond Technique (WRT) Training Centre for CPP Training And Services Sdn Bhd at Unit 17, USJ 10/1E Taipan Triangle, Subang Jaya, Selangor Darul Ehsan / Sharifah Rosnani Syed Mohd - Syed Mohd, Sharifah Rosnani (Faculty of Architecture, Planning and Surveying, 2012)
For the final project of the interior design, student needs to understand about the process and the important technique about designing. For this report proposed about New Interior Design of Women Respond Technique (WRT) Training centre for CPP Training and Services Sdn.Bhd. at unit 17, USJ 10/1E Taipan Triangle, Subang Jaya, Selangor Darul Ehsan. This project proposed to create a centre for Woman Respond Technique (WRT) agency. This centre also to teach women how to defense themselves. The aim of this project is to provide a centre with facilities and activities that specific for women to learn about self-defense technique. This project also makes the development for a new space planning with the good arrangement. To complete the requirement for this project, interview with client, do site analysis, research and observation has been done.